Invisible wounds: The impacts of mastectomy on women´s self-image (Research, Society and Development, 2021)
The performance of mastectomy in women brings up negative feelings and perceptions about their self-image, which consequently affects self-esteem and corroborates problems related to sexuality and social relationships. The study aims to identify through the scientific literature the repercussions on the self-image of mastectomized women. This is an integrative literature review with a qualitative approach, carried out in the database, LILACS and in the VHL and SCIELO libraries. The Health Sciences Descriptors: Women's Health, Mastectomy and Self-image were used, which were crossed simultaneously with the Boolean operator AND. The selection of articles used the inclusion and exclusion criteria as a basis, and a final sample of eight references was selected to compose the study. After withdrawing the breast, women showed feelings of despair, disorientation, upset, inferiority, fear of death, embarrassment in sexual relations and loss of libido. Regarding self-image, sadness stands out, as it is understood that breast removal will affect femininity. The need to develop strategies aimed at preparing women who will undergo mastectomy is evident, aiming at minimizing psychological distress and improving their quality of life.